Nilai Moral Penanaman Ari-Ari Di Setra Pada Desa Kedisan Kecamatan Kintamani Kabupaten Bangli - Ida Ayu Komang Arniati; I Wayan Sukarma; Ida Ayu Surya Wahyuni (Jurnal Penelitian Agama Hindu, 2019)
The purpose of the study is to find out, understand, and analyze and interpret the reason the placenta was planted in Setra (cemetery). This research was conducted in Kedisan Village, Kintamani District, Bangli Regency. Data is collected from observations, interviews and documents relevant to research. Data analysis techniques are descriptive, qualitative and interpretive. An in-depth analysis of placenta planting in Setra for the Kedisan villagers, and found several reasons (1) Sociological reasons, the act of planting the placenta in Setra in Kedisan Village for; (a) Fostering Togetherness, is a manifestation of a sense of devotion to the ancestors and respect for the rules that exist in the Village of Kedisan. This is realized through close cooperation between villagers and can increase a sense of togetherness and respect for tradition; (b) Respect to Ancestors, Kedisan villagers feel the need to purify and preserve the placenta planting in Setra Bebajangan as a religious activity that has spiritual power (taksu). With the trust and confidence of Kedisan villagers, they did not dare to oppose and violate what their ancestors had done in planting the placenta or placenta in Setra Bebajangan. (2) Religious reasons, namely; (a) realizing the Nature of Life as a Human, humans as one of God's creations have the most important and most noble position because humans have the ability to increase their dignity and status, so as to distinguish between good behavior and bad behavior; (b) The existence of Pura Dalem Bebajangan, located to the west of the village surrounded by Kedisan State Elementary School and Pura Dalem Kahuripan coincide at the intersection of Kedisan Village which serves to worship Lord Shiva, with His personification as Sang Hyang Panca Korsika, Sanghyang Catur Sanak, and Sanghyang Kumara.